Propylthiouracil and peripheral neuropathy - Valentina Van Boekel; José Maurício Godoy; Luiz A. Lamy; Samira Assuf; João G. Corrêa Meyer Neto; Salim L. Balassiano; Luiz E. Prata (Arquivos de Neuro-Psiquiatria)
Peripheral neuropathy is a rare manifestation in hyperthyroidism. We describe the neurological manifestations of a 38 year old female with Graves' disease who developed peripheral neuropathy in the course of her treatment with propylthiouracil. After the drug was tapered off, the neurological signs disappeared. Therefore, we call attention for a possible toxic effect on peripheral nervous system caused by this drug.